Gambaran Kepercayaan Diri Perawat dalam Mengatasi Agresi Pasien di Rumah Sakit Jiwa - Achmad Syamsudin; Ah Yusuf; Mundakir Mundakir (FORIKES, 2020)
Background: Nurses as the staff who are around 24 hours near the patient to provide nursing care are very at risk of experiencing unexpected behavior in the form of aggressive behavior. This can affect the nurse's confidence in patient care, absenteeism, and turnover. Methods: This research was a quantitative research using a descriptive-analytic approach, to found a description of demographic and the level of confidence of nurses in conducting aggressive behavior management. Results: Based on the respondent demographic characteristics, it was found that the majority of respondents were male, aged >35 years old, educated with Associate’s degree, had work periods ranging from >5-10 years, were level 2 of clinical nurses, were civil servants, and work in the VIP room. The majority of nurses' confidence in dealing with patient aggression was at a